Time-dependent nanoscale plasticity in nanocrystalline nickel rods and tubes. (February 2016) - Lee, Jung-A; Seo, Brandon B.; Choi, In-Chul; Seok, Moo-Young; Zhao, Yakai; Jahed, Zeinab; Ramamurty, Upadrasta; Tsui, Ting Y.; Jang, Jae-il
Abstract: Time-dependent nanoscale plasticity of nanocrystalline nickel at room temperature was critically explored through a series of micropillar creep and quasi-static compression experiments on rod and tube specimens fabricated by electron beam lithography and electroplating. Enhanced creep rates in tubes as compared to rods, establishes the facilitating role played by the free surface in time-dependent deformation. Creep stress exponent, n, and strain-rate sensitivity, m, were compared to examine connections between creep and the rate-dependent plasticity, if any. Graphical abstract: